2017
DOI: 10.2196/ijmr.5075
|View full text |Cite
|
Sign up to set email alerts
|

Internet Usage by Parents Prior to Seeking Care at a Pediatric Emergency Department: Observational Study

Abstract: BackgroundLittle is known about how parents utilize medical information on the Internet prior to an emergency department (ED) visit.ObjectiveThe objective of the study was to determine the proportion of parents who accessed the Internet for medical information related to their child’s illness in the 24 hours prior to an ED visit (IPED), to identify the websites used, and to understand how the content contributed to the decision to visit the ED.MethodsA 40-question interview was conducted with parents presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 27 publications
6
33
1
1
Order By: Relevance
“…It has been reported that 43–56% of parents of children presenting to emergency departments (EDs) had searched online for health information at some time, 1 3 and that 6–12% had undertaken a health‐related search before taking their child to an ED 1 . ‐ 3 How such behaviour affects the doctor–patient relationship during an ED consultation is poorly understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that 43–56% of parents of children presenting to emergency departments (EDs) had searched online for health information at some time, 1 3 and that 6–12% had undertaken a health‐related search before taking their child to an ED 1 . ‐ 3 How such behaviour affects the doctor–patient relationship during an ED consultation is poorly understood.…”
mentioning
confidence: 99%
“…The implications It may be beneficial for doctors to acknowledge and discuss health-related internet searches with adult emergency department patients. I t has been reported that 43e56% of parents of children presenting to emergency departments (EDs) had searched online for health information at some time, [1][2][3] and that 6e12% had undertaken a health-related search before taking their child to an ED. [1][2][3] How such behaviour affects the doctorepatient relationship during an ED consultation is poorly understood.…”
mentioning
confidence: 99%
“…This measurement is problematic because it would require parents to remember their exact query terms, the rank order of results, and the exact sites that were visited within a specified time period prior to their visit. One survey of parents who accessed the Internet 24 h prior to an ED visit found that over one-third of parents could not remember any visited website (3). Thus, relying on a parent's memory to analyze visited websites might be inaccurate.…”
Section: Limitationsmentioning
confidence: 99%
“…Up to 56% of RECEIVED: 20 February 2019; FINAL SUBMISSION RECEIVED: 5 May 2019; ACCEPTED: 4 June 2019 parents perform online searches prior to bringing their child to the emergency department (ED), with 68% of queries containing symptoms and 51% containing treatment options (2). Nearly one in eight parents use the Internet to search health information immediately prior to visiting an ED (3).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the family seeks online data as a way to complement the knowledge of professionals, not to replace it; since the elements sought help in the care provided at home. Therefore, it is important to guide the use of reliable resources to support such care (14) and guide subjects in relation to health information available in that environment (10) .…”
Section: Introductionmentioning
confidence: 99%